Heterocycle-based dynamic covalent chemistry for dynamic functional materials - Zeyu Ma; Siyu Pan; Yang Yang; Yuan Zeng; Bo Wang; Yen Wei; Lei Tao (Nature Communications)
Abstract Dynamic covalent chemistry, which renders reusable and degradable thermoset polymers, is a promising tool for solving the global problem of plastic pollution. Although dynamic covalent chemistry can construct dynamic polymer networks, it rarely introduces other functions into polymers, which limits the development of dynamic functional materials. Herein, we develop heterocycle-based dynamic covalent chemistry and demonstrate the reversibility of the aza-Michael addition reaction between functional heterocycle dihydropyrimidin-2(1H)-thione and electron-deficient olefins. Our method produces a degradable linear polymer and recyclable and self-healable crosslinked polymers similar to traditional dynamic covalent chemistry, but the heterocycles endow the polymer with excellent ultraviolet-blocking and high-energy blue light-blocking abilities, and tunable fluorescence and phosphorescence properties. These are difficult to create with ordinary dynamic covalent chemistry. This proof-of-concept study provides insights into heterocycle-based dynamic reactions, and may prompt the development of dynamic chemistry and dynamic functional materials.